PENGARUH GAYA KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN MELALUI KOMITMEN ORGANISASI PADA DINAS PENDIDIKAN PEMUDA DAN OLAHRAGA KABUPATEN SIKKA - Taufik Arifin; murjali moa rodja (Jurnal GeoEkonomi, 2021)
The purpose of this study was to examine the influence of situational leadership styles on employee performance through a commitment to the Sikka District Youth and Sports Education Office. The number of samples in this study was 60 employees taken using saturated sampling or census sampling. Data were collected through a questionnaire distributed to 60 employees of the Office of Youth and Sports Education in Sikka Regency; 60 questionnaires were collected again which were taken by the census. In this study, the validity test was performed by Pearson's product-moment correlation technique. The analysis technique used in data processing is multiple regression analysis and hypothesis testing using the classic assumption test, f test, and t-test as the basis for decision making. The results showed that there was no significant effect between leadership style and employee performance, with a t value of only -0.812 through the t-test. But there is a direct effect of the intervening variable of organizational commitment on employee performance where the t value of 2.222 is greater than the value of t table 2.004. The leadership style does not have a direct influence on employee performance and it turns out that through the f test it was found that it is more effective with the indirect effect mediated by intervening variables of organizational commitment. While the direct and indirect relationship of organizational culture has significant results on employee performance, it means that organizational culture has a significant influence on improving employee performance at the Department of Youth and Sports Education in Sikka Regency